Control of the Hypoxic Response in Drosophila melanogaster by the Basic Helix-Loop-Helix PAS Protein Similar - Lavista Llanos, Sofía (2002)
In mammalian systems, the heterodimeric basic helix-loop-helix (bHLH)-PAS transcription hypoxia-inducible factor (HIF) has emerged as the key regulator of responses to hypoxia. Here we define a homologous system in Drosophila melanogaster, and we characterize its activity in vivo during development. By using transcriptional reporters in developing transgenic flies, we show that hypoxia-inducible activity rises to a peak in late embryogenesis and is most pronounced in tracheal cells. We show that the bHLH-PAS proteins Similar (Sima) and Tango (Tgo) function as HIF-alpha and HIF-beta homologues, respectively, and demonstrate a conserved mode of regulation for Sima by oxygen. Sima protein, but not its mRNA, was upregulated in hypoxia. Time course experiments following pulsed ectopic expression demonstrated that Sima is stabilized in hypoxia and that degradation relies on a central domain encompassing amino acids 692 to 863. Continuous ectopic expression overrode Sima degradation, which remained cytoplasmic in normoxia, and translocated to the nucleus only in hypoxia, revealing a second oxygen-regulated activation step. Abrogation of the Drosophila Egl-9 prolyl hydroxylase homologue, CG1114, caused both stabilization and nuclear localization of Sima, indicating a central involvement in both processes. Tight conservation of the HIF/prolyl hydroxylase system in Drosophila provides a new focus for understanding oxygen homeostasis in intact multicellular organisms.